Knowledge and Attitudes of Pregnant Women Toward Iron Supplementation During Pregnancy in the Work Area of Pegasing Health Center Central Aceh in 2021 - Hidayana; Sri Wahyuni MS; Nova Ratna Dewi (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background: This study aims to determine the extent of knowledge and attitudes of pregnant women toward the consumption of iron tablets in the working area of Pegasing Health Center, Pegasing District, Central Aceh Regency, in 2021. Methods: This research is descriptive research. The research sample was 35 pregnant women in the working area of Pegasing Health Center. Data were collected and measured using a questionnaire of 40 questions, 20 questions about knowledge, and 20 questions about attitudes. Results: The mother's knowledge about the definition and need for iron is in the sufficient category (41.86%), the impact of iron deficiency is in a good category (74.29%) the purpose of giving iron is in the good category (57.14%) containing a source of iron is in the sufficient category (65.71%) while the attitude of pregnant women to the consumption of iron tablets is in a good category (42.86%). Conclusion: Most of the respondents have a sufficient level of knowledge regarding the definition, benefits, and food sources of iron during pregnancy. Most pregnant women are well aware of the impact of iron deficiency and the purpose of iron tablet supplementation during pregnancy. The majority of respondents have a good attitude towards iron supplementation during pregnancy.